Effective treatment for symptomatic brain tumours and arteriovenous malformation in children by radiosurgery with a rotating gamma system - Khoa Mai Trong; Phuong Pham Cam; Luan Nguyen Duc; Hung Nguyen Quang; Phuong Dao Manh; Thai Pham Van (Vietnam Journal of Science, Technology and Engineering, 2022)
To assess the effectiveness of radiosurgery with a rotating gamma system (RGS) for paediatric brain tumours and arteriovenous malformation (AVM), this work was carried out on 123 patients with brain tumours or AVM received radiosurgery at Bach Mai hospital. The median dose was 13 Gy from a range of 8 to 20 Gy. Endpoints include the effects of increased intracranial pressure, seizures, hemiplegia, and tumour size on the syndrome. Results exhibited that the percentages of patients with complete response, partial response, and disease progression out of 59 patients with headache accounted for 11.9, 69.5, and 18.6%, respectively. Of the 20 patients with seizures, 30% had complete response, 65% partial response, and 5% stable disease. Regarding brain tumour size, 9 months after treatment, those with complete response, partial response, stable disease, and disease progression made up 18.7, 50.4, 14.6, and 16.3% of the total patients, respectively. There was no statistically significant effect of radiation dose on the results. This study showed a high percentage of children with brain tumours and AVM undergoing radiosurgery with a RGS had symptomatic responses after treatment.